The Menhuan System and the Unification of Muslim Communities in Western China - Mehad Mousa (Penerbit Hellow Pustaka, 2025)
This study mainly investigates the objectives of the Menhuan system, a unique Sufi organization in western China, to determine its role in unifying Muslim communities in Gansu, Ningxia, and Qinghai. Using historical analysis, the methods involve examining the cultural, political, and religious factors that shaped the system's development. The research concludes that the Menhuan system was a crucial mechanism for integrating diverse ethnic groups into a cohesive socio-religious framework. A significant finding is that its hierarchical and hereditary nature, while a source of unity, also generated internal tensions.this research further discusses the system's contemporary legacy, underscoring its enduring relevance to modern Chinese Muslim identity and community structures.